Relating aerosol mass spectra to composition and nanostructure of soot particles. (February 2019) - Malmborg, Vilhelm B.; Eriksson, Axel C.; Török, Sandra; Zhang, Yilong; Kling, Kirsten; Martinsson, Johan; Fortner, Edward C.; Gren, Louise; Kook, Sanghoon; Onasch, Timothy B.; Bengtsson, Per-Erik; Pagels, Joakim
Abstract: The composition and carbon nanostructure of soot are important parameters influencing health and climate effects, and the efficacy of soot mitigation technologies. We used laser-vaporization, electron-ionization aerosol mass spectrometry (or SP-AMS) to systematically investigate relationships between aerosol mass spectra, carbon nanostructure (HRTEM), and composition (thermal-optical carbon analysis) for soot with varying physicochemical properties. SP-AMS refractory black carbon concentrations (based on C ≤ 5 + clusters) were correlated to elemental carbon (r = 0.98, p < 10 −8 ) and equivalent black carbon (aethalometer) concentrations. The SP-AMS large carbon ( C ≥ 6 +, midcarbons and fullerene carbons) fraction was inversely correlated to fringe length (r = −0.97, p = 0.028) and linearly correlated to the fraction of refractory organic carbon that partially pyrolize during heating (r = 0.89, p < 10 −4 ). This refractory organic carbon material was incompletely detected with conventional aerosol mass spectrometry (flash vaporization at 600 °C). This suggests that (SP-AMS) refractory carbon cluster analysis provides insight to chemical bonding and nanostructures in refractory carbon materials, lowcarbons ( C ≤ 5 + ) indicate mature soot and large carbons indicate refractory organic carbon and amorphous nanostructures related to C5 -components. These results have implications for assessments of soot particle mixing state and brown carbon absorption in the atmosphere and enable novel, on-line analysis of engineered carbon nanomaterials and soot characteristics relevant for climate and health. Graphical abstract: Image 1